Association of intestinal malrotation and Bochdalek hernia in an adult: a case report - Salústio, Raquel (BioMed Central, 2014)
BACKGROUND: Late presentations of congenital diaphragmatic hernia are rare and differ from the classic neonatal presentation. The association with other congenital malformations in children, mainly intestinal malrotation, is well documented. The diagnosis of this association in adults is very rare, and depends on a high degree of suspicion. CASE PRESENTATION: We report a case of a 50-year-old female Caucasian patient with a previous history of intestinal malrotation diagnosed in adolescence and treated conservatively. She was referred to the hospital with signs and symptoms of intestinal obstruction. The patient undertook computed tomography that confirmed small bowel obstruction with no obvious cause, and a right subphrenic abscess with right empyema was also present. An exploratory laparotomy was performed that revealed an intestinal malrotation associated with a right gangrenous and perforated Bochdalek hernia. Resection of the affected small bowel, closure of the Bochdalek foramen and the Ladd procedure were carried out. CONCLUSION: This case shows a rare association of two rare conditions in adults, and highlights the challenge in reaching the diagnosis and management options.